2007
DOI: 10.1525/aeq.2007.38.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Swimming: On Oxygen, Resistance, and Possibility for Immigrant Youth under Siege

Abstract: In this article, we consider the ways in which educational policies and institutions today enable or obstruct young people who are immigrant English‐language learners as they seek to cross cultural and educational borders. Contrasting a class action suit in California protesting high stakes testing that will significantly limit graduation rates, and an ethnographic analysis of the international high schools in which immigrant youth engage with cultural and educational depth and support and graduate at exceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…All of these elements echo the literature on school structures and practices that foster refugee students' success (for example, Bajaj & Bartlett, 2017;Bartlett et al, Forthcoming;Fine & Jaffe-Walter, 2007;Fine et al, 2005;Mendenhall et al, 2017).…”
Section: Discussionmentioning
confidence: 70%
“…All of these elements echo the literature on school structures and practices that foster refugee students' success (for example, Bajaj & Bartlett, 2017;Bartlett et al, Forthcoming;Fine & Jaffe-Walter, 2007;Fine et al, 2005;Mendenhall et al, 2017).…”
Section: Discussionmentioning
confidence: 70%
“…There is also research that describes situations in school where adolescent Latinas are verbally and physically harassed by their U.S.-born peers who claim to not understand their spoken English (Fine, Jaffe-Walter, Pedraza, Futch, & Stoudt, 2007;Olsen, 2008). In her ethnographic study of a California high school, Olsen (2008) observed that first-generation Latina youth experience daily occurrences of being laughed at for incorrect English, being made fun of for heavy accents, and having difficulty finding their way around school when they do not understand English.…”
Section: Language Ideologiesmentioning
confidence: 99%
“…Hostility from the broader environment has been given less attention in the general youth programs literature, as it may be assumed that schools or communities support, or at least are not openly hostile toward, youth programs. However, for settings that work with stigmatized populations such as LGBT youth, a hostile external context may matter and may bring about youth activism (Fine & Jaffee-Walter, 2007). Therefore, school-level hostility to LGBT youth could be a key factor that shapes the activities and experiences of GSAs and similar groups that engage in activism to challenge systems of inequality (e.g., through deliberate awareness-raising efforts to challenge heterosexism and invisibility or by directly countering acts of discrimination; Mayberry, 2006; Miceli, 2005).…”
Section: Variability Across Gsas In Overall Socializing and Advocacymentioning
confidence: 99%